2005
DOI: 10.1128/jcm.43.6.3009-3010.2005
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Breast Abscess Caused by Gordonia bronchialis in an Immunocompetent Patient

Abstract: We present the first reported case of a recurrent breast infection caused by Gordonia bronchialis. The infection occurred in a 43-year-old immunocompetent female, and species level identification was obtained with 16S rRNA sequencing. CASE REPORTA 43-year-old female presented to hospital with a 4-day history of a tender mass in her left breast. On examination, there was marked fullness with erythema on the lateral aspect of the left breast extending to the areola and a palpable mass measuring 4 to 5 cm in diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…bronchialis, the species isolated in this case, was initially identified from samples of soil and sputum from patients with pulmonary disease (Conville & Witebsky, 2001;Johnson et al, 2011;Siddiqui et al, 2012). Only 13 cases of infection with this species of actinomycete have been described (Siddiqui et al, 2012), including a reported recurrent breast abscess in an immunocompetent patient with no previous medical history (Werno et al, 2005) that shared many features with our case. Another case of granulomatous mastitis in an immunocompetent patient caused by other species of Gordonia (Gordonia terrae) has also been reported, although the patient had a previous history of nipple piercing (Zardawi et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…bronchialis, the species isolated in this case, was initially identified from samples of soil and sputum from patients with pulmonary disease (Conville & Witebsky, 2001;Johnson et al, 2011;Siddiqui et al, 2012). Only 13 cases of infection with this species of actinomycete have been described (Siddiqui et al, 2012), including a reported recurrent breast abscess in an immunocompetent patient with no previous medical history (Werno et al, 2005) that shared many features with our case. Another case of granulomatous mastitis in an immunocompetent patient caused by other species of Gordonia (Gordonia terrae) has also been reported, although the patient had a previous history of nipple piercing (Zardawi et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
“…(Werno et al, 2005). Many patients, as in our case, require 6-12 weeks of therapy with different antibiotics, often along with appropriate surgical debridement (Johnson et al, 2011;Siddiqui et al, 2012;Sng et al, 2004;Werno et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations